Effect of Employee Characteristics and Organizational Culture on Employee Performance Mediated By Motivation - Hery Winoto Tj (Quantitative Economics and Management Studies, 2022)
Human resources are important factors that need to be considered by companies, with superior human resources, the company has the potential to achieve its goals effectively and efficiently. Besides that, the company can also win the competition and expand its business. This study aims to analyze the effect of employee characteristics and organizational culture on employee performance with motivation as a mediating variable. Using the purposive sampling technique, the respondents obtained are 125 employees of PT Nuansa Bumi. The technique used in analyzing the data in this research is Non-Probability sampling using SmartPLS tools. The results obtained from this study are that employee characteristics and organizational culture positively affect employee performance. Employee characteristics and organizational culture mediated by motivational ​​variable also positively affect employee performance.